A relação entre subjetividade e transcendência : a luta contra o psicologismo nas investigações lógicas - Alves, Tayrone Barbosa Justino (Universidade Federal de São Carlos, 2015)
The aim of this work is to clarify the problematic relationship between subjectivity and transcendence in the Logical Investigations of Edmund Husserl. To this end, we draw a genesis of this problem, from the period prior of this work in question, until the end of his explicitness on Prolegomena. Such problematic relationship arises in Husserl combat against the psychologists conceptions of the end of sec. XIX, and, we sustain, is the biggest concern of this author throughout the course of the Investigations. What we will show in our work is how at the end of refutation of psychologism, is left to Husserl explain how can subjectivity and transcendence get in relation, since Prolegomena put such instances as separate natures, the legacy problem to the rest of the Investigations is to show how an act of judgment, which is a subjective experience, the subject enters into a relationship with the object judged by this act, the instance that transcends such subjectivity. The Husserl's answer is to present a discipline, phenomenology, which seeks to describe within the subjective, in the experiences of knowledge, the essence of the modes this subjective dimension refer to objects that transcend itself. We will explain how even after denying psychologist attempt, such a notion operates negatively throughout elaboration of the phenomenological method, that is, the phenomenology is as an overcoming of psychologism, in its most fundamental flaws.
The Relationship between Subjectivity and Transcendence: The Fight against Psychologism in the Logical Investigations
Keywords: Fenomenologia; Psicologismo; Subjetividade; Transcendência; Conhecimento; Phenomenology; Psichologism; Subjectivity; Transcendence; Knowledge; CIENCIAS HUMANAS::EDUCACAO